KEMAMPUAN BERAKAR STEK PUCUK DARI BEBERAPA KLON Pinus merkusii KANDIDAT BOCOR GETAH - Gunawan Nugrahanto; Mochamad Naiem; Sapto Indrioko; Eny Faridah; Widiyanto Widiyanto (Jurnal Pemuliaan Tanaman Hutan, 2019)
Pinus merkusii sap is one of Indonesia's superior NTFP products with high economic value. Increasing the sap productivity through the uses of geneticaly improved material of high resin yielder pinus, referred as “Pinus Bocor Getah” (PBG), is necessary. Vegetative propagation technique could used to obtain the high productivity of PBG in shorter times. This research aims to observe the rooting ability of PBG clones through a callus shoot cuttings technique. Of the 24 clones observed, 14 clones were taken from the hedge orchards and 10 clones were from selected tree in progeny test. Two experimental design used are completely randomized block designs and completely random design. Observation on the rooting ability includes parameters of the success rate of rooted, height increase, number and length of primary roots, number and length of secondary roots, root volume, root biomass and shoot and root ratio. The results showed that all tested clones showed ability to perform rooted shoot cutting, but the percentage rate of rooting varied among the clones. Amount of 71.42% clones from hedge orchard were rooted above 50% with Clone Pkp 9 and Pkp 13 as the highest percentage of rooting ( 93.75%). For the clones from progeny test, only one clone of Ppt 17 was rooted at above 50% (82.08%). The clones were significantly affected the primary root length and the number of secondary roots, especially for the clones from hedge orchard. The highest primary root length was found in Clone Pkp 3 (66.38 cm), and the highest number of secondary roots was found in Clone Pkp 14 (39). Other observed parameters were not significantly affeted by the difference of clones. The results of the study indicate that some PBG clones have the potential to be further developed massively through clonal propagation techniques.